Pemanfaatan TIK Dalam Pembuatan Dokumen Pendukung Untuk Melamar Pekerjaan Pasca Kelulusan Siswa SMK Di Kab. Tanah Bumbu - Rijal Surya Rahmany; Yongki Christandi Batubara; I Made Ivan Wiyarta Cakra Sujana; Gad Gunawan; Diniar Mungil Kurniawati; Chaerul Qalbi AM; Jefri Aldo; Muhammad Hariz Dedy Sayogi (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Vocational high school (SMK) students represent a level of vocational secondary education expected to fulfill the demand for technical labor at specific levels within the industry. However, current SMK graduates face challenges due to intense competition in securing employment. This community service initiative aims to enhance the skills of SMK students by focusing on the utilization of Information and Communication Technology (ICT) in the preparation of post-graduation documents. A case study was conducted at a private vocational high school (SMKS) in and state vocational high school (SMKN) in Tanah Bumbu Regency as an effort to prepare students to face the challenges of Industry 4.0. Through outreach activities, this initiative introduced the concept of community service and the benefits of ICT in document preparation. The methods employed aimed to achieve outcomes such as improving students' skills, applying ICT in preparing supporting documents for job applications, and enhancing students' competitiveness in the labor market. The results of the activities carried out showed an increase in participants' knowledge of curriculum vitae and job application letters. Survey results also indicated that the seminar was highly beneficial for participants in this community service activity through technical outreach.